Dentine Replacement with Biodentine Under Class II Composite Inlay: A Case Report - Lora Mishra1, Pratayee Basu2, Sumit Dash1, Naomi Ranjan Singh3, Rini Behera3 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Biodentin is a bioactive cement with dentin-like mechanical properties, which can be used as a dentinesubstitute for both crown and root. It also helps in the remineralization of dentine along with maintenanceof pulp vitality. This advocated to be used in various clinical applications, such as root perforations,apexification, resorptions, retrograde fillings, pulp capping procedures, and dentine replacement. Indirectlaboratory-processed composite systems present an esthetic alternative for intracoronal posterior restorationsand provide esthetic results that may also reinforce tooth structure. Additional clinical benefits include exactmarginal integrity, wear resistance similar to enamel, wear compatibility with opposing natural dentition,optimal esthetics, ideal proximal contacts, and excellent anatomic morphology.